Rancang Bangun Sistem Penjualan Furniture Berbasis Web Dengan Metode Prototype - Gina Apriasiska; Juni Nurma Sari (ABEC Indonesia, 2022)
Edi Furniture is a business that is engaged in furniture and furniture and has been running for about 30 years. Many buildings such as schools, health centers, police houses, and other buildings have furniture and furniture made in Edi Furniture. Many contractors are already clients of Edi Furniture. However, payments and data processing are still done manually. That way we need a system that can process the furniture sales process online, can provide information from wood processing to completion, and process data obtained from the sales process in the form of order reports, payment reports, product reports, and Inventory reports. The solution to this problem is the construction of a system "Design and Build a Web-Based Furniture Sales System with the Prototype Method". This system can facilitate the product marketing process, can carry out the sales process easily and efficiently, and can perform data processing quickly and precisely. This system uses black box testing and usability testing. The development of this system was completed in 2 iterations and the system worked for approximately 4 months. Based on the results of black box testing, it can be concluded that the functionality of the system has been successful. Meanwhile, based on questionnaire testing on users, it was found that 81.11% of this system was satisfactory for users, and based on questionnaire testing on employees it was found that 88% of this system was satisfactory for employees.